2020
DOI: 10.1002/adsc.202000195
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Hydroxide‐Catalyzed Asymmetric Allylation of Acetophenones with Amido‐Functionalized Allylboronate in Water

Abstract: Enantioselective allylation of aldehydes and ketones is a widely used approach for preparing chiral homoallylic alcohols, however, most of the reactions are still mainly performed in organic solvents. Considering their environmental impact, expansion of synthetic technology in water has the highest priority in the organic chemistry field. Here, we report enantioselective reaction of water‐stable amido‐functionalized allylboronates with acetophenone derivatives in water. The reaction was catalyzed with zinc hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…More recently, we focused on the remarkable air-and water-stability of 1 and developed enantioselective allylation of acetophenones catalyzed by a zinc-chiral aminophenol system in water. [3] Although these results show the utility of 1 on allylation of carbonyl compounds not only in organic solvents but also in water, its synthetic application is still limited to 1,2-addition to carbonyl groups. In this paper, we report a new copper-catalyzed enantioselective amide-functionalized allylation of maleimide derivatives, which expand the utility of 1 to 1,4-addition.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…More recently, we focused on the remarkable air-and water-stability of 1 and developed enantioselective allylation of acetophenones catalyzed by a zinc-chiral aminophenol system in water. [3] Although these results show the utility of 1 on allylation of carbonyl compounds not only in organic solvents but also in water, its synthetic application is still limited to 1,2-addition to carbonyl groups. In this paper, we report a new copper-catalyzed enantioselective amide-functionalized allylation of maleimide derivatives, which expand the utility of 1 to 1,4-addition.…”
Section: Introductionmentioning
confidence: 93%
“… [2b,c] In this case, the reaction proceeded in the presence of zinc bromide and potassium carbonate to furnish the 1,2‐adducts which could be used as a common precursor for three types of spiro compounds. More recently, we focused on the remarkable air‐ and water‐stability of 1 and developed enantioselective allylation of acetophenones catalyzed by a zinc‐chiral aminophenol system in water [3] . Although these results show the utility of 1 on allylation of carbonyl compounds not only in organic solvents but also in water, its synthetic application is still limited to 1,2‐addition to carbonyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…Most of asymmetric allylations of carbonyl compounds and derivatives are performed in organic solvents. In 2020, Yoda et al reported a rare example of enantioselective allylation of ketones 81 carried out in water at room temperature [51]. It employed as allylating agent water-stable amido-functionalized allylboronate 82.…”
Section: Allylationsmentioning
confidence: 99%
“…Generally, good results were achieved in the reaction of acetophenones (56-98% ee) with higher ee values for ortho-substituted substrates (70-98% ee) than Scheme 24. Allylation of ketones with an amido-functionalized allylboronate in water and in the presence of a tertiary amine ligand [51].…”
Section: Allylationsmentioning
confidence: 99%
“…Our research group succeeded the enantiopure synthesis of these compounds, in which enantioselective allylation of an isatin derivative with an amido-functionalized allylstannane was employed as a key reaction (Scheme 1b) [10,11]. More recently, an amide-functionalized allyl boronate was developed as an alternative reagent for the allylstannane [12][13][14][15][16], which led to the syntheses of not only cytotoxic methylene-lactones spiro-fused to a lactam Scheme 1: Examples of (a) bioactive compounds bearing an α-methylene-γ-butyrolactone structure, (b) syntheses of spirocyclic compounds through nucleophilic amide allylation, and (c) syntheses of spirocyclic compounds through electrophilic amide allylation.…”
Section: Introductionmentioning
confidence: 99%